Intraoperative intracardiac thrombus in liver transplantation: A 9‐year retrospective review focusing on treatment and outcomes. Issue 10 (9th May 2022) - Fagelman, Erica; Wang, Ryan; Tomlinson, Amanda; Romano, Diana; Schlichting, Nicolette; Zerillo, Jeron; DeMaria,, Samuel; Smith, Natalie K.
Abstract: This study characterizes incidence and outcomes surrounding intracardiac thrombosis (ICT) during liver transplantation over 9 years at a single center before and after the routine use of transesophageal echocardiography (TEE). Adult liver transplantation patients from 2011 to 2020 were divided into eras based on routine TEE use. ICTs were identified by querying anesthetic records for search terms. Descriptive statistics included counts and proportions for baseline recipient, donor, intraoperative, and postoperative characteristics. Outcome data were based on date of hospital discharge and date of death. The incidence of ICT increased in the TEE era (2016–2020) compared with the pre‐TEE era (2011–2015; 3.7% [25/685] vs. 1.9% [9/491]; p < 0.001). Patients with ICT had significantly higher Model for End‐Stage Liver Disease–sodium (MELD‐Na) scores, pretransplant hospitalization, malignancy, drug‐induced liver injury, hypertension, deep vein thrombosis, reperfusion syndrome, transfused platelets and cryoprecipitate, and use of hemostatic medications. A higher proportion of patients in the ICT group underwent simultaneous liver–kidney transplantation. The patients with ICT were similar, except patients in the pre‐TEE era had higher MELD‐Na scores and incidences of hepatitis C virus and lower incidences of encephalopathy. In the pre‐TEE era, all ICTs presented as intraoperative cardiac arrest, and the 30‐day mortality in the setting of ICT was 66.7% (6/9). During the TEE era, 80% of ICTs were diagnosed incidentally or attributed to hemodynamic instability ( p = 0.002). The 30‐day mortality rate was 36% (9/25) in the TEE era ( p = 0.25). ICT incidence increased in the TEE era, yet the mortality rate was lower, suggesting that routine intraoperative TEE may lead to the early detection of ICT prior to hemodynamic collapse.